HABITAÇÃO DE INTERESSE SOCIAL E TECNOLOGIA: DA PRODUÇÃO EM MASSA PARA A CUSTOMIZAÇÃO - Miranda, Erica de Matos; Dezen-kempter, Eloisa (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The lack of harmony between the standardization of Housing Units (HU) from the current Public Housing Programs (PHP) and the demands of the residents shows the need to incorporate concepts of flexibility and adaptability into the unit design, aiming at its evolutionary customization. To address these issues, a research was driven to analyze the shape and layout arrangement of the HU and the possibilities of spatial relationship and adaptability of a standard unit (SU) to fit the demands of different family patterns. Therefore, a case study was carried out with a project of the Program Minha Casa, Minha Vida (PMCMV) implemented in the Administrative Region of Campinas. A field survey was applied using the Stated Preference (SP) technique to identify the current situation of the dwellings, the satisfaction degree with the HU delivered, and the desired and/or implemented adaptations. The results show that despite the resident's satisfaction with the HU, they wanted to make changes to fit the specific needs of the family. Based on this perspective, changes in the design was propose, which allowed the residents to adapt the HU for a competitive sale price (PV) compared with the current houses of the PMCMV.